Stepping up to the mark? Firms' export activity and environmental innovation in 14 European countries - Finn Ole Semrau; Aoife Hanley (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We investigate how a firm's export activity and country idiosyncrasies determine the firm's adoption of environmental innovation (EI) as well as the firm's decision to extend its number of EI typologies. To this end, we append two waves of the Community Innovation Survey, differentiate our sample of 14 European countries into advanced and less-advanced countries, merge the resulting data with export statistics from theWorld Input-Output Tables and apply a hurdle negative binomial model. In a finding new to the literature, we reveal heterogeneous effects in how the firm's export activity determines its EI adoption decision, depending on the country the firm is based and which foreign market the firm serves. We do not find any export destination independent environmental premium to export activity for firms based in an advanced country, which replicates prior studies mainly focusing on single countries. Conversely, for firms based in less-advanced countries, we observe that increased export activity boosts EI adoption and the number of EI typologies adopted. Moreover, our empirical analysis reveals for firms based in both country groups that exports towards environmentally demanding countries boost EI, while there is no environmental premium of exports towards emerging countries. The importance of the direction of trade provides a novel perspective on regulation-push and demand-pull mechanisms as determinants of EI adoption, normally investigated for domestic markets, and in our paper extended to foreign markets with a different set of stakeholders preferences...
Keywords: F18; O31; Q52; Q56; 330; Green/eco-/environmental innovation; Environment and trade; Export destination; Sustainable Development Goals 9 and 12